2016
DOI: 10.18632/aging.100901
|View full text |Cite
|
Sign up to set email alerts
|

Exercise: a “new drug” for elderly patients with chronic heart failure

Abstract: Patients with chronic heart failure (CHF) experience progressive deterioration of functional capacity and quality of life (QoL). This prospective, randomized, controlled trial assesses the effect of exercise training (ET) protocol on functional capacity, rehospitalization, and QoL in CHF patients older than 70 years compared with a control group. A total of 343 elderly patients with stable CHF (age, 76.90±5.67, men, 195, 56.9%) were randomized to ET (TCG, n=170) or usual care (UCG, n=173). The ET protocol invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 30 publications
1
32
0
3
Order By: Relevance
“…Overall, these findings contribute to explain the molecular mechanisms underlying the benefits induced by PA and support the prescription of personalized ET to elderly CHF patients as an effective and safe "drug" (Antonicelli et al, 2016).…”
Section: Resultssupporting
confidence: 53%
“…Overall, these findings contribute to explain the molecular mechanisms underlying the benefits induced by PA and support the prescription of personalized ET to elderly CHF patients as an effective and safe "drug" (Antonicelli et al, 2016).…”
Section: Resultssupporting
confidence: 53%
“…Exercise is seen as a diagnostic and prognostic tool as well as a therapeutic intervention in CHF [195]. Several trials have shown that exercise is beneficial for CHF [196][197][198][199][200], not only improving functional capacity and the QoL but also reducing the risk of rehospitalization, even showing a tendency towards better survival rates. Moreover, both poor and intermediate self-reported physical activity were associated with a higher risk of HHF and mortality [201].…”
Section: Future Directions In Finding Novel Treatments For Hfmentioning
confidence: 99%
“…Since epigenetic modifications are reversible, affecting gene expression without altering the DNA sequence, recently we activated a line of research aimed to assess the impact of lifestyles, such as exercise and diet, on aging processes [2,3,34,63]. Although in vivo detection and targeting of senescent cells are still being investigated, it is likely that therapeutic strategies based on antioxidant and anti-inflammatory compounds would involve generalized anti-aging effects [59].…”
Section: The New Program On Aging and Age-related Diseases (Ards): Idmentioning
confidence: 99%